The spillover of euro area shocks to the Maltese economy - William Gatt; Germano Ruisi (Central Bank of Malta, 2022)
This paper develops a two-block Structural Vector Autoregression (SVAR) to estimate the spillover of external shocks to the Maltese economy. The model focuses on five broad macroeconomic shocks hitting the euro area; an aggregate demand shock, two aggregate supply shocks which respectively proxy better overall productivity and more favourable conditions on the global market for oil, a generic monetary policy shock encompassing both conventional and unconventional interventions, and a financial stress shock. The model is estimated using Bayesian methods over a sample that goes from 2003Q1 to 2019Q4 and considers a number of Maltese variables that are representative of both the real and the financial side of the economy. The results point toward a relevant role of the identified shocks in explaining the fluctuations of the Maltese economy with particular regard to the aggregate demand and financial stress shocks. Overall, shocks hitting the euro area are estimated to contribute to around one third of the fluctuations of the Maltese output and prices in the long run.
Keywords: C11; C32; E32; F41; 330; Bayesian SVAR; block exogeniety; shock spillover; monetary policy; historical decomposition